Las Redes Sociales Aplicadas a las Pymes. Caso (Frisby, Selva negra, Jeno’s pizza y Habana club) - Andrade Osorio, Jorge Enrique (Ciencias Administrativas, Económicas y Contables, 2018)
The marketing digital has become a fundamental tool for the development of marketing strategies, to be a cornerstone in the relationship between organizations and their markets; the digital marketing plays a significant part in the business processes of the companies, due to the integration of new information and communication technologies, which play a major part in the development of new forms of sale. This uses the advertising online as a tool to promote a product or service using digital tools such as links, banners, pop up, Taglines, Advectorial, Insterstical, Layers, microsite, ciberpost, among others as google trends used to identify the most wanted content on the website by the sector to which it will direct. Allowing companies create new ideas and relevant content, taking advantage of trends and thus win more customers.